Blue-green cities : integrating urban flood risk management with green infrastructure - Thorne, C. R. (ICE Publishing, 2020)
This work demonstrates how urban flood risk management based on blue-green approaches and infrastructure can deliver both sustainable flood risk management and multiple co-benefits that are valued by urban communities.